Water quality of an Ecuadorian Andean stream with the use of aquatic macroinvertebrates. (UNED Research Journal, 2016)
Ecuador is crossed by a network of rivers that originate mainly in the high Andean reliefs and pour into two basins: Amazon and Pacific. Many suffer from severe human impact. The main objective of the present study was to assess water quality of Mojarrero stream using biotic indices (BMWP/Col. and Shannon-Wiener index) as a tool to evaluate ecosystem health. During June, August and October 2014, bottom samples were taken at three stations. Each month and season three replicates of benthic aquatic invertebrates were taken on sandy-stony bottoms with a 0,3 mm mesh “D-net”. The fauna was represented by eleven orders and 29 families. The most abundant order was Coleoptera, representing 42,70% of total collected organisms, followed by Diptera (19,01%) and Ephemeroptera (11,38%). The most abundant family was Elmidae, with 568 individuals, (37,37% of total organisms), followed by Chironomidae (11,38%) and Baetidae (7,24%). Shannon diversity values ranged between 0,98 bits/ind. (June, EST. 2) and 2,23 bits/ind. (October, Est 1). The BMWP/Col. index values indicate that the river has a good environmental health on the high and low sections. The median section has some pollution, particularly during August and October.
Keywords: freshwater macro invertebrates; stream quality; IBMWP/Col; Andean stream; Ecuador.